Exploration of Sustainable Live Fish Business in Nepal - Devkota, Hareram; Jha, Dilip Kumar; Joshi, Tista Prasai; Shrestha, Shreemat; Bhandari, Mahendra Prasad; Poudel, Nabaraj (Journal of Agriculture and Environment, 2023)
Live fish businesses are likely to become more popular in Nepal due to their reliable source of food. The live fish food survey data was collected from a Google Form questionnaire in the Nepalese language. This study investigates consumers, retailers, and wholesalers in Nepal's live fish market to identify significant concerns that could be addressed in the decision-making of live fish professionals. Nonparametric tests are used for non-normally distributed data, and parametric tests are used for normally distributed data. The study found high mortality and administrative obstacles of 68.60% and 48.60%, respectively. If the wrong choice of aeration method and equipment is made, more fish will survive in the retailer's shop and during transportation time. Fish Models II and III will be an alternative to the current method of transportation, which shows that increasing the tank capacity by one standard deviation increases fish survival by 0.7 and 0.65 standard deviations, respectively. To increase the dissolved gas, the survey suggests that transportation and aeration methods should be improved. This increases the volume of transportation while using the same resources, meeting market demands.